Shunted magnetostrictive devices in vibration control. (25th August 2020) - Deng, Zhangxian; Scheidler, Justin J; Asnani, Vivake M; Dapino, Marcelo J
Abstract: Structural vibrations in rotating machinery may lead to imprecise motion control, excessive noise, or even structural damage. Magnetostrictive materials can dissipate unwanted vibrations via hysteresis, eddy currents, and joule heating while exhibiting an electrically-tunable elastic modulus. Harnessing this feature, this article presents a shunted magnetostrictive device that includes an iron-gallium (Galfenol) rod, a permanent magnet array, a flux return path, and shunt circuits. The stiffness tunability and damping of this passive device are measured under a 750 Hz sinusoidal axial compression for resistive, capacitive, and inductive shunt circuits. The effect of eddy currents stiffness and damping is investigated for the first time by comparing results from laminated and solid Galfenol rods. Solid Galfenol produces larger eddy current-based damping, while laminated Galfenol enables larger stiffness variation and total damping. This device demonstrates a power density of 19.83 mW cm −3 for vibration energy harvesting. The frequency-dependent behavior of the shunted device is tested from 5 Hz to 1 kHz for selected electrical loads.